2003
DOI: 10.1177/000348940311200709
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nasal Polyps in Adults: The Skovde Population-Based Study

Abstract: Patients with nasal polyps present repeatedly in otorhinolaryngology practices, but the prevalence of nasal polyps in the general population is not known. Our objective was to investigate the prevalence of nasal polyps in an adult Swedish population in relation to age, gender, asthma, and aspirin intolerance. A random sample of 1,900 inhabitants over the age of 20 years, stratified for age and gender, was drawn from the municipal population register in Skövde, Sweden, in December 2000. The subjects were called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
141
5
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(179 citation statements)
references
References 12 publications
15
141
5
13
Order By: Relevance
“…They can even be clinically silent. 5 In our study we found nasal obstruction (87%) and nasal discharge (71%) to be the most common symptoms of patients with nasal polyps. Other symptoms were sneezing, snoring, headache, loss of smell as in Table 3.…”
mentioning
confidence: 47%
“…They can even be clinically silent. 5 In our study we found nasal obstruction (87%) and nasal discharge (71%) to be the most common symptoms of patients with nasal polyps. Other symptoms were sneezing, snoring, headache, loss of smell as in Table 3.…”
mentioning
confidence: 47%
“…El gráfico de la derecha muestra la comparación de las unidades HU obtenidas en los cornetes a los diferentes días del proceso de inducción de la RSC-PN…………………………………………………………………………………………………... 16 …”
Section: Figuraunclassified
“…Por otra parte, la presencia de PN puede venir acompañada de la sintomatología propia de los mismos o, por el contrario, de forma silente, siendo este último tipo de pólipos de carácter permanente o transitorio. Este hecho implica que existe una clase de pacientes en los que no se contempla la existencia de PN hasta que son descubiertos mediante exploración clínica [16]. A estos pacientes que por carecer de sintomatología no son propensos a diagnosticarles la existencia de PN se debe añadir el hecho de que aproximadamente un tercio de los pacientes sintomáticos de la enfermedad no solicitan atención médica al aparecer los síntomas nasosinusales [17].…”
Section: Epidemiología De La Enfermedadunclassified
“…Já no grupo abaixo de 20 anos encontramos apenas um caso de PN (grupo não-asmático), esse achado é concordante com os dados da literatura, de baixa prevalência de PN nas duas primeiras décadas de vida (Rugina et al 2002, Johansson et al 2003.…”
Section: Idadeunclassified
“…Esse resultado está de acordo com aqueles encontrados na literatura, com predomínio do sexo masculino (Moloney 1977, Voegels 1998, 2001e 2002, Larsen e Tos 2002, Rugina et al 2002, Johansson 2003.…”
Section: Sexounclassified